LAS COMPETENCIAS DE LA GENERALITAT DE CATALUÑA EN MATERIA DE PROTECCIÓN PÚBLICA DE MENORES - Ángeles de Palma del Teso (Revista d'Estudis Autonòmics i Federals, 2007)
Legal institutions for the public protection of minors are at present regulatedby regulations enacted as civil legislation. This study looks at the reasonswhy this was the case. Catalan legislators continued down the road that Spanish state legislators had travelled beforehand. In fact, by this meansSpanish state legislators sought, and to a large extent succeeded in, unifying,standardising and including the regulations in this area into commonlaw. This process of "making civil" a task of the government had createddistortions, ranging from some decreases in citizen's guarantees when dealingwith the Government to considerable legal uncertainty. That is why itwould be wise to retrace our steps to make the government's work interms of the protection of minors more administrative. It is the right timeto do so. A process reforming the legislation for public protection of minorsis now under way in Catalonia. First, the Department of Justice is producinga draft law which will approve the second book of the Catalonia CivilCode, which regulates the protection of minors. At the same time, theDepartment of Social Action and Citizenship has begun the process to enacta new Law regulating childhood and adolescence. These legal texts willtherefore regulate the public and private institutions protecting minors anda legal regime will be established for them. The Civil Code should regulatethe legal/private institutions for the protection of minors, under the jurisdictionof civil legislation (art. 129 of the Statute of Autonomy of Catalonia).However, the legal and public institutions for the protection of minors shouldbe regulated within a governmental framework, as social services and publicprotection of minors (art. 166 of the Statute of Autonomy of Catalonia).Despite this, to the extent that the private and public institutions for theprotection of minors are interrelated, the two regulations must complementeach other. This is beside the fact that a civil law contains administrative regulations;this is not the problem. The issue is clearly establishing the legalregime of the legal/public institutions for the protection of minors. TheGovernment's work in terms of the public protection of minors must besubject to administrative law, insofar as the Government acts as a publicauthority, i.e. by exercising the prerogatives that the regulation confers onit to satisfy public interests, such as the protection of children.